SWOT ANALYSIS OF BOGOR CAREER CENTER COLLABORATIVE GOVERNANCE PROGRAM IN THE EMPLOYMENT SERVICE IN BOGOR DISTRICT - Syahrudin, Dede; Setiawan, Koesworo; Sa'diah, Halimatu; Salsabila, Vidya Zahra; Seran, Gotfridus Goris; Salbiah, Euis; Apriliani, Afmi; Saepudin; Munjin, R. Akhmad (Universitas Djuanda, 2025)
Bogor Career Center (BCC) is a program from the Bogor Regency Manpower Office to improve job opportunities and workforce skills. However, the effectiveness of this program still faces challenges, such as synergy between stakeholders, limited resources, and workforce readiness in facing industrial competition. This study aims to analyze the SWOT factors in the implementation of collaborative governance in the BCC program and measure its effectiveness which emphasizes trust, communication, and implementation capacity, as well as analysis that includes program success, target achievement, user satisfaction, input-output levels, and overall goal achievement. This study uses qualitative methods with interview techniques, documentation studies, and observations. The results of the study indicate that BCC has strengths in policy support and partnership networks, but still faces coordination constraints and resource limitations. The opportunities for this program lie in the utilization of technology and industry collaboration, while the threats include labor market dynamics and budget constraints. The analysis shows that trust and communication between stakeholders still need to be strengthened, and implementation capacity is not optimal. In terms of effectiveness, target achievement and user satisfaction still need to be improved to ensure the sustainability of the program. In conclusion, the success of collaborative governance in the BCC program depends on strengthening trust, communication, and implementation capacity, as well as the effectiveness of the program in achieving targets and user satisfaction.